2021
DOI: 10.3389/fbioe.2021.649317
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Wound Closure Acceleration in a Patient With Toxic Epidermal Necrolysis Using a Lyophilised Amniotic Membrane

Abstract: Background: Toxic epidermal necrolysis (TEN) is a rare life-threatening disease that mainly affects the skin and mucous membranes, resulting from a toxic delayed-type hypersensitivity (DTH) reaction (type IV reaction) to the presence of foreign antigens such as drugs. The clinical symptoms are caused by pathophysiological processes leading to massive apoptosis of keratinocytes in the dermo-epidermal junction. This results in the formation of a bulla and subsequent separation of the entire epidermis with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…This can protect the dermis and promote wound healing. 58 We found that patients with 5+ SCORTEN had a mortality rate of 62.5%. This conflicts with the current estimated SCORTEN mortality of >90%.…”
Section: Discussionmentioning
confidence: 69%
“…This can protect the dermis and promote wound healing. 58 We found that patients with 5+ SCORTEN had a mortality rate of 62.5%. This conflicts with the current estimated SCORTEN mortality of >90%.…”
Section: Discussionmentioning
confidence: 69%
“…Existem diversas atualizações nos tratamentos com medidas experimentais que demonstram algum resultado, como o uso de derivados de membrana amniótica para cobrir a superfície corporal. (Roviello et al, 2019;Lipový et al, 2021).…”
Section: Resultsunclassified
“…There are several updates in treatments with experimental measures that demonstrate some results, such as the use of amniotic membrane derivatives to cover the body surface. (Roviello et al, 2019), (Lipový et al, 2021).…”
Section: Resultsmentioning
confidence: 99%